Superconducting State Parameters of Binary Superconductors - Aditya M. Vora (Журнал нано- та електронної фізики)
A well known pseudopotential is used to investigate the superconducting state parameters viz. electron-phonon coupling strength , Coulomb pseudopotential *, transition temperature ТС, isotope effect exponent  and effective interaction strength N0V for the AgxZn1 – x and AgxAl1 – x binary superconductors theoretically for the first time. We have incorporated here five different types of the local field correction functions to show the effect of exchange and correlation on the aforesaid properties. Very strong influence of the various exchange and correlation functions is concluded from the present study. The comparison with other such experimental values is encouraging, which confirms the applicability of the model potential in explaining the superconducting state parameters of binary mixture.